Young Emiratis’ uses and gratifications of mobile news and storytelling - Shamseldien, Fathy Mohamed; Abdelkareem, A. Nasir Yousuf; Okela, Abdelmohsen Hamed; Aseda, Muhammed Abdelaziz Said Taha (Frontiers in Communication, 2025)
This study examines the mobile news and storytelling consumption patterns of young Emiratis, employing the Uses and Gratifications Theory (UGT) to elucidate their motives and favored platforms. UGT asserts that individuals deliberately choose media to satisfy specific needs, emphasizing gratifications such as information, entertainment, and social interaction. The study indicates a notable trend among young Emiratis who select mobile devices for news and storytelling, with 95.3% of respondents identifying mobile phones as their primary source. Data was gathered from 400 students using self-reported surveys, supplemented by five focus group discussions consisting of six to eight students each from Al Wasl University. The findings reveal that 82.6% of participants expressed a strong interest in mobile news and storytelling. The dimension of interactivity emerged as a significant source of gratification and is strongly associated with storytelling consumption. The results underscore the considerable influence of mobile devices on the media consumption habits of young Emiratis and suggest opportunities for enhancing interactive storytelling in digital journalism.